2022
DOI: 10.31083/j.fbl2709266
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQA1 and DQB1 Alleles are Associated with Acitretin Response in Patients with Psoriasis

Abstract: Background: Psoriasis vulgaris is an immune-mediated inflammatory skin disease. Although the pathogenesis of psoriasis is unclear, genetic susceptibility, such as HLA-C*06:02, is believed to be a major risk factor. However, there is a paucity of knowledge regarding the relationship between genetics and the response to systemic treatment of psoriasis. We hypothesized that genetic variations in human leukocyte antigen (HLA) genes may act as predictors of acitretin treatment in psoriasis. The aim of our study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In the present study, the following 92 novel genomic markers for psoriasis were identified through GWAS and PRS ( Table SI ). Additionally, 61 previously reported genomic markers associated with psoriasis in Taiwanese populations were identified ( Table SI ): ATP binding cassette subfamily F member 1 ( 47 ), advanced glycosylation end-product specific receptor ( AGER ) ( 48 ), allograft inflammatory factor 1 ( 49 ), Annexin A6 ( 50 ), butyrophilin-like 2 ( BTNL2 ) ( 51 ), complement C2 ( 52 ), chromosome 6 open reading frame 15 ( 53 , 54 ), complement factor B ( 52 , 55 ), fibroblast activation protein α ( 56 ), HLA complex group 26 ( 57 ), HLA complex group 27 ( 57 ), HLA complex group 9 ( 58 ), HLA complex P5 ( 59 , 60 ), HLA complex P5B ( 59 , 60 ), major histocompatibility complex, class I, A ( HLA-A ) ( 61 ), major histocompatibility complex, class I, B ( HLA-B ) ( 62 , 63 ), major histocompatibility complex, class I, C ( HLA-C ) ( 53 , 54 ), major histocompatibility complex, class II, DM β ( HLA-DMB ) ( 64 ), major histocompatibility complex, class II, DQ α1 ( HLA-DQA1 ) ( 65 ), major histocompatibility complex, class II, DQ α2 ( HLA-DQA2 ) ( 66 ), major histocompatibility complex, class II, DQ β1 ( HLA-DQB1 ) ( 67 ), major histocompatibility complex, class II, DR β1 ( HLA-DRB1 ) ( 67 ), major histocompatibility complex, class I, E ( HLA-E ) ( 68 ), major histocompatibility complex, class I, F ( HLA-F ) ( 69 ), major histocompatibility complex, class I, G ( HLA-G ) ( 70 ), heat shock protein family A ( Hsp70 ) member 1A ( HSPA1A/HSPA1B ) ( 71 ), Hsp70 member 1-like ( ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the following 92 novel genomic markers for psoriasis were identified through GWAS and PRS ( Table SI ). Additionally, 61 previously reported genomic markers associated with psoriasis in Taiwanese populations were identified ( Table SI ): ATP binding cassette subfamily F member 1 ( 47 ), advanced glycosylation end-product specific receptor ( AGER ) ( 48 ), allograft inflammatory factor 1 ( 49 ), Annexin A6 ( 50 ), butyrophilin-like 2 ( BTNL2 ) ( 51 ), complement C2 ( 52 ), chromosome 6 open reading frame 15 ( 53 , 54 ), complement factor B ( 52 , 55 ), fibroblast activation protein α ( 56 ), HLA complex group 26 ( 57 ), HLA complex group 27 ( 57 ), HLA complex group 9 ( 58 ), HLA complex P5 ( 59 , 60 ), HLA complex P5B ( 59 , 60 ), major histocompatibility complex, class I, A ( HLA-A ) ( 61 ), major histocompatibility complex, class I, B ( HLA-B ) ( 62 , 63 ), major histocompatibility complex, class I, C ( HLA-C ) ( 53 , 54 ), major histocompatibility complex, class II, DM β ( HLA-DMB ) ( 64 ), major histocompatibility complex, class II, DQ α1 ( HLA-DQA1 ) ( 65 ), major histocompatibility complex, class II, DQ α2 ( HLA-DQA2 ) ( 66 ), major histocompatibility complex, class II, DQ β1 ( HLA-DQB1 ) ( 67 ), major histocompatibility complex, class II, DR β1 ( HLA-DRB1 ) ( 67 ), major histocompatibility complex, class I, E ( HLA-E ) ( 68 ), major histocompatibility complex, class I, F ( HLA-F ) ( 69 ), major histocompatibility complex, class I, G ( HLA-G ) ( 70 ), heat shock protein family A ( Hsp70 ) member 1A ( HSPA1A/HSPA1B ) ( 71 ), Hsp70 member 1-like ( ...…”
Section: Resultsmentioning
confidence: 99%
“…The antigenic peptides contained in each HLA molecule are unique, despite some overlap in binding specificities ( 111 , 112 ). Certain HLA alleles, such as HLA-A ( 61 ), HLA-B ( 62 , 63 ), HLA-C ( 53 , 54 ), HLA-DMB ( 64 ), HLA-DQA1 ( 65 ), HLA-DQA2 ( 66 ), HLA-DQB1 ( 67 ), HLA-DRB1 ( 67 ), HLA-E ( 68 ), HLA-F ( 69 ) and HLA-G ( 70 ), are more prevalent in patients with psoriasis. The findings of the present study indicated a significant association between the genetic variability of HLA -related genes located on chromosome 6 and the development of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Among 100 Chinese individuals, those who were positive for the DQA10201 allele demonstrated a more favorable response to acitretin compared to those who were negative for the same allele. (PASI75 at 2 months, p = 0.001) [ 37 ].…”
Section: Treatmentmentioning
confidence: 99%
“…HLA-DQB1 alleles have been mentioned to involve in genetic predisposition to psoriasis vulgaris in the Slovak population [ 38 ]. In 100 Chinese patients, the DQB1*0202 -positive patients showed a better response to acitretin than the DQB1*0202 -negative patients (PASI75 at 2 months, p = 0.005) [ 37 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Contradictory results have been received regarding the association between the VEGFA rs833061 variant and acitretin response with a similar sample size [ 46 , 47 ], while negative results were reported regarding APOE [ 48 ] and IL36RN [ 49 ] SNPs, implying the assessment of patient subgroups according to additional disease-associated loci. Indeed, deep sequencing of the HLA locus uncovered several loci associated with the treatment response (n = 24), with the HLA-DQA1*:02:01, DQB*:02:02 showing the same association signals in the validation set (n = 76) [ 50 ]. Variants mapped to ion transporters were also documented to discriminate acitretin responsiveness of 151 Chinese Han psoriasis patients, while functional experiments showed that the SLCO1B1 rs4149056 C allele reduced the acitretin uptake, resulting in improved treatment efficacy [ 51 ].…”
Section: Traditional Therapiesmentioning
confidence: 99%